Sawdust-biomass based materials for sequestration of organic and inorganic pollutants and potential for engineering applications - Kayode Adesina Adegoke; Oreoluwa Ololade Adesina; Omolabake Abiodun Okon-Akan; Oyeladun Rhoda Adegoke; Abdullahi Biodun Olabintan; Oluwaseyi Aderemi Ajala; Halimat Olagoke; Nobanathi Wendy Maxakato; Olugbenga Solomon Bello (Current Research in Green and Sustainable Chemistry, 2022)
Sawdust materials are global wastes obtained from wood processing and exploitation activities. They are usually dumped/stored in uncontrolled conditions, thus becoming a major contributor to environmental pollution. Over the years, drastic efforts have been placed on converting these materials to a carbon source that can be applied for wastewater treatment. This places value on sawdust usage to ensure a green, clean, and sustainable environment thereby contributing to the global waste management system. The present review aims at presenting an empirical analysis and methodological approaches on sawdust-biomass-based material for the adsorptive removal of different pollutants from an aqueous solution. The first few parts revealed the hope and fate of sawdust-biomass-based materials in the environment, the health effects of sawdust on human and aquatic lives, and the environmental effects. This study further presents the source, types, composition, fabrication and configuration of sawdust adsorbents and characterization of the adsorbents derived from sawdust-biomass-based materials. The categories of pollutants considered in this study were grouped into endocrine-disrupting chemicals, dyes, pesticides, herbicides and agrochemicals, and heavy metals. A comprehensive review and the corresponding performance of sawdust-biomass-based adsorbents for each pollutant category was presented independently, and comparisons was made in each class. Adsorption capacity of different sawdust-based adsorbents ranged from 10 to 667.9 ​mg/g (for endocrine-disrupting chemicals and other emerging contaminants removal), 69.44–372 ​mg/g (for pesticides, herbicides, and agrochemicals removal), 3.42–526.3 ​mg/g (for dyes removal) and 2.87–325 ​mg/g (for heavy metal removal). This study further discussed the adsorption mechanisms of these materials, strategies for enhancing the efficiency of sawdust-biomass-based adsorbents and a potential methodological approach for engineering application, which is absent in the literature. Lastly, this study highlighted important observations and conclusions relating to the knowledge gaps to foster the way forward for the materials towards ensuring more industrial applications.